Artemisia absinthium L. Aqueous and Ethyl Acetate Extracts: Antioxidant Effect and Potential Activity In Vitro and In Vivo against Pancreatic α-Amylase and Intestinal α-Glucosidase - Asmae Hbika; Nour Elhouda Daoudi; Abdelhamid Bouyanzer; Mohamed Bouhrim; Hicham Mohti; El Hassania Loukili; Hamza Mechchate; Rashad Al-Salahi; Fahd A. Nasr; Mohamed Bnouham; Abdelhamid Zaid (MDPI AG, 2022)
Artemisia absinthium L. is one of the plants which has been used in folk medicine for many diseases over many centuries. This study aims to analyze the chemical composition of the Artemisia absinthium ethyl acetate and its aqueous extracts and to evaluate their effect on the pancreatic α-amylase enzyme and the intestinal α-glucosidase enzyme. In this study, the total contents of phenolic compounds, flavonoids, and condensed tannins in ethyl acetate and the aqueous extracts of Artemisia absinthium leaves were determined by using spectrophotometric techniques, then the antioxidant capacity of these extracts was examined using three methods, namely, the DPPH (2, 2-diphenyl-1picrylhydrazyl) free radical scavenging method, the iron reduction method FRAP, and the β-carotene bleaching method. The determination of the chemical composition of the extracts was carried out using high-performance liquid chromatography-the photodiode array detector (HPLC-DAD). These extracts were also evaluated for their ability to inhibit the activity of the pancreatic α-amylase enzyme, as well as the intestinal α-glucosidase enzyme, in vitro and in vivo, thus causing the reduction of blood glucose. The results of this study showed that high polyphenol and flavonoid contents were obtained in ethyl acetate extract with values of 60.34 ± 0.43 mg GAE/g and 25.842 ± 0.241 mg QE/g, respectively, compared to the aqueous extract. The results indicated that the aqueous extract had a higher condensed tannin content (3.070 ± 0.022 mg EC/g) than the ethyl acetate extract (0.987 ± 0.078 mg EC/g). Ethyl acetate extract showed good DPPH radical scavenging and iron reduction FRAP activity, with an IC50 of 0.167 ± 0.004 mg/mL and 0.923 ± 0.0283 mg/mL, respectively. The β-carotene test indicated that the aqueous and ethyl acetate extracts were able to delay the decoloration of β-carotene with an inhibition of 48.7% and 48.3%, respectively, which may mean that the extracts have antioxidant activity. HPLC analysis revealed the presence of naringenin and caffeic acid as major products in AQE and EAE, respectively. Indeed, this study showed that the aqueous and ethyl acetate extracts significantly inhibited the pancreatic α-amylase and intestinal α-glucosidase, in vitro. To confirm this result, the inhibitory effect of these plant extracts on the enzymes has been evaluated in vivo. Oral intake of the aqueous extract significantly attenuated starch- and sucrose-induced hyperglycemia in normal rats, and evidently, in STZ-diabetic rats as well. The ethyl acetate extract had no inhibitory activity against the intestinal α-glucosidase enzyme in vivo. The antioxidant and the enzyme inhibitory effects may be related to the presence of naringenin and caffeic acid or their synergistic effect with the other compounds in the extracts.